Promotion of catalytic performance of Mn–Ce/biochar catalysts in SCR reaction by ultrasonic treatment. (June 2022) - Xu, Junchao; Liu, Haoxin; Sun, YunLan; Chu, Huaqiang; Lv, Li; Zheng, Zhimin; Wu, Yuxin
Abstract: A series of Mn–Ce oxide catalysts loaded on KOH activated biochar (BCK), which were prepared by the traditional impregnation method (TI) or ultrasonic impregnation method (UI), were studied to examine the selective catalytic reduction (SCR) of NO at low temperature. The results indicated that the catalysts prepared by the UI possessed better catalytic performance than the catalysts prepared by the TI, especially the catalyst prepared by the UI with higher loading amount exhibited well low-temperature catalytic activity. The physicochemical properties of all the catalysts were investigated by N2 adsorption-desorption, SEM, XRD, FTIR, NH3 -TPD, and XPS. It revealed that Mn–Ce/BCK(UI) exhibited a higher specific surface area (SSA) and ratios of Ce 3+, Mn 4+, and Oβ, as well as a better dispersibility of Mn–Ce oxides on the catalyst surface. Moreover, FTIR illustrated that there were more adsorbed oxygen species on the surface of Mn–Ce/BCK(UI). The above results were further verified by multifractal analysis which presented that ultrasonic treatment could promote the dispersion of metal oxides on the catalyst surface. It could be concluded that the UI might be a better choice than the TI in the process of preparing high loading catalysts. Graphical abstract: Image 1 Highlights: Ultrasonic treatment improves the metal loading amount of carbon-based catalysts. Multifractal theory was introduced to analyze the surface features of catalysts. Ultrasonic treatment improves the self-similarity of the catalyst surface. The SCR reaction exists simultaneously "standard SCR" and "fast SCR".